2012
DOI: 10.7708/ijtte.2012.2(4).03
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian Crossing Speed: The Case of Malaysia

Abstract: Pedestrians are vulnerable road users, and they are always at risk when making their daily trips. Hence, roadway design and tra c control devices need to consider pedestrians' safety. Pedestrian walking speed is fundamental to any roadway and tra c control design. Unfortunately, no speci c guidelines exist for pedestrian crossing speed in Malaysia. e ultimate goals of this research are to establish the local pedestrian crossing speed and to identify the contributing factors. A total of 1579 samples on pedestri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 6 publications
2
11
1
3
Order By: Relevance
“…[13,19,[29][30][31] and unsignalized intersections [19,26,32,33]. Previous studies found that male pedestrians were significantly faster than female pedestrians while crossing the road [13,19,26,[29][30][31][32][33][34][35]. While observing the impact of age on crossing speed, previous studies suggest that with the increase of the age, pedestrian crossing speed tends to slow down [13,19,26,29,30,32,34,35].…”
Section: Literature Reviewmentioning
confidence: 97%
See 4 more Smart Citations
“…[13,19,[29][30][31] and unsignalized intersections [19,26,32,33]. Previous studies found that male pedestrians were significantly faster than female pedestrians while crossing the road [13,19,26,[29][30][31][32][33][34][35]. While observing the impact of age on crossing speed, previous studies suggest that with the increase of the age, pedestrian crossing speed tends to slow down [13,19,26,29,30,32,34,35].…”
Section: Literature Reviewmentioning
confidence: 97%
“…Mean speed in different countries [19]. [13,19,[29][30][31] and unsignalized intersections [19,26,32,33]. Previous studies found that male pedestrians were significantly faster than female pedestrians while crossing the road [13,19,26,[29][30][31][32][33][34][35].…”
Section: Literature Reviewmentioning
confidence: 97%
See 3 more Smart Citations